P.082 The Toronto Concussion Study: The Feasibility and Effects of Early Prescribed Aerobic Exercise on Recovery and Post-Concussive Symptoms in Adults – A Pilot Study. (November 2021) - Foster, E; Kempenaar, A; Chandra, T; Lawrence, D; Inness, EL; Langer, L; Danells, C; Comper, P; Bayley, M
Abstract : Background: Evidence suggests that aerobic exercise (AE) soon after concussion may facilitate earlier recovery in athletes. The purpose of this pilot study was to investigate the feasibility and effects of early sub-symptom threshold AE on symptom trajectory and recovery time in a heterogeneous adult population. Methods: Adults presenting within 7 days of concussion were randomized to either the experimental group: prescribed AE (90% of symptom-limited heartrate achieved on Buffalo Concussion Treadmill Test [BCTT]), 30 minutes/day, 5 days/week, or the control group: standard of care exercise recommendations. Participants were assigned a heartrate monitor bracelet to track activity. They underwent serial treadmill testing to monitor exercise tolerance, update prescriptions and determine recovery. Results: 20 participants (10 per arm) completed the BCTT protocol within 7 days of injury, with 8/20 demonstrating exercise tolerance at week 1. 66% (4/6) of those in the experimental group were recovered by week 4, compared to only 43% (3/7) in the control group. Average heart rate monitor compliance was 32% of the prescribed time among all participants, and self-reported exercise prescription compliance was 43% in the experimental group. Conclusions: Early post-concussion aerobic exercise in the general adult population is a promising intervention; this study will inform the design of a larger trial.